2018
DOI: 10.1002/lary.27554
|View full text |Cite
|
Sign up to set email alerts
|

Familial unilateral vestibular schwannoma is rarely caused by inherited variants in the NF2 gene

Abstract: Objectives/Hypothesis Unilateral vestibular schwannoma (VS) occurs with a lifetime risk of around 1 in 1,000 and is due to inactivation of the NF2 gene, either somatically or from a constitutional mutation. It has been postulated that familial occurrence of unilateral VS occurs more frequently than by chance, but no causal mechanism has been confirmed. Study Design Retrospective database analysis. Methods The likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Few population-based studies have reported the prevalence of sporadic VS in recent years. 3,7,16 To estimate the lifetime prevalence of sporadic VS in a clinical setting-that is, during routine clinical practice with modern neuroimaging capabilities, not through review of temporal bones at autopsy-the chance that a person sporadically develops a VS exceeds 1 in 500. 3 As the resolution of MRI continues to improve, the clinical prevalence will likely gradually approach historical temporal bone studies that have cited lifetime prevalence as high as 1 in 100 persons.…”
Section: Discussionmentioning
confidence: 99%
“…Few population-based studies have reported the prevalence of sporadic VS in recent years. 3,7,16 To estimate the lifetime prevalence of sporadic VS in a clinical setting-that is, during routine clinical practice with modern neuroimaging capabilities, not through review of temporal bones at autopsy-the chance that a person sporadically develops a VS exceeds 1 in 500. 3 As the resolution of MRI continues to improve, the clinical prevalence will likely gradually approach historical temporal bone studies that have cited lifetime prevalence as high as 1 in 100 persons.…”
Section: Discussionmentioning
confidence: 99%
“…The role of mutation screening for NF2 in all patients with a unilateral vestibular schwannoma is less certain. Although these patients show an increased risk for the development of NF2, routine screening for germline mutations is not recommended except in patients younger than 30 years [ 65 , 66 ], but can undergo prenatal diagnosis and pre-implantation genetic diagnosis.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…An example of this is the variant in the splice donor site of intron 8, NC_000022.11 (NM_006767.3):c.791+1G>A, was recently detected in peripheral lymphocytes and tumor tissue of a patient presenting solely with unilateral vestibular schwannoma at age 14 (Gripp et al, 2017). A similar, more recent study in patients with unilateral vestibular schwannoma reported two VUS in LZTR1 , NM_006767.3:c.1230C>T and NM_006767.3:c.1687G>C, with the potential of affecting splicing, as predicted by in silico tools (Evans et al, 2019).…”
Section: Introductionmentioning
confidence: 63%